Bioactives of noni plant (Morinda citrifolia L.) as anti-cancer herbals: A scoping review - Kujariningrum, Oktavia Beni; Winarni, Sri; Cahyani, Kharisma Olivia Anugrah; Anggitasari, Nadia Puji; Azizah, Waviq (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
In Indonesia, the noni plant (Morinda citrifolia L.) has gained popularity as an alternative treatment for various diseases. Cancer is the second cause of death worldwide, with chemotherapy as the primary treatment. There is growing interest in exploring phytochemicals found in noni plants such as anthraquinones, chitosan, phenols, and flavonoids. These antioxidant compounds hold potential as alternative treatments for cancer. This study explores the active compounds in noni plants that exhibit anti-cancer properties. This study employed a scoping review approach. Previous original articles were retrieved from Scopus, Science Direct, ClinicalKey, Springer Link, and Google Scholar with keywords in Morinda citrifolia L., component, bioactive, antioxidant, anti-inflammatory, and anti-cancer. We included 34 articles that met the inclusion criteria. The findings of this study highlight the anti-cancer activity of several phytochemicals found in noni plants. Damnacanthal has been shown to reduce the number of MCF-7 cells. Nordamnacanthal inhibited the development of the H400 cell cycle by increasing the activity of Cytochrome C, Caspase-9, and Caspase 3/7 and induced the death of MDA-MB231 and MCF-7 cells. Chitosan nanoparticles can inhibit the growth of A549 cells. Scopoletin can inhibit cancer cell proliferation by inducing cells in the G0 / G1 and S phases. Epicatechin can inhibit the growth of PC-9 cells. Damnachanthal, nordamnacanthal, chitosan nanoparticles, scopoletin, and epicatechin are active compounds presented in noni plants that can act as anti-cancer.